Dynamics of Peripheral Lymphocyte Subsets from Birth until Old Age - Nawal A. B. Taher; Johana M. Isaza-Correa; Ashanty M. Melo; Lynne A. Kelly; Alhanouf I. Al-Harbi; Mary I. O’Dea; Zunera Zareen; Emer Ryan; Murwan Omer; Liam Townsend; Eleanor J. Molloy; Derek G. Doherty (Immuno)
The immune system is inexperienced before birth and tends to be tolerogenic, rather than immunogenic. After birth, the adaptive immune system develops while facing microbial challenges, but it can become impaired as old age progresses and persistent inflammation can lead to chronic morbidity, disability and frailty. To investigate the potential contributions of lymphocyte subsets to immunity from birth until old age, we enumerated circulating innate and conventional lymphocytes and measured serum cytokine levels in 10 cord blood samples and in peripheral blood from 10 healthy term neonates, 23 healthy school-age children, 25 young adults and 11 older subjects. Flow cytometric analysis revealed that B cell frequencies increase during childhood and gradually decrease into adulthood, whereas natural killer cell frequencies increase throughout life. T cell frequencies remained relatively constant throughout life, as did their expression of CD4 and CD8. However, all four innate T cell populations studied—invariant natural killer T cells, mucosa-associated invariant T cells and the Vδ1 and the Vδ2 subsets of γδ T cells—were extremely rare in cord blood and in peripheral blood of neonates, but they expanded after birth reaching highest levels in adulthood. Analysis of serum cytokine levels revealed that proinflammatory and T helper type 1 (Th1) cytokine levels increase in adulthood, whereas Th2 and Th17 cytokine levels remain relatively constant. These changes in lymphocyte numbers and cytokine levels across the lifetime are likely to affect immunocompetence, leaving newborn and elderly people susceptible to infection, cancer and immune-mediated disease.